تقويم نوافذ الصيرفة الإسلامية- دراسة حالة الجزائر: Evaluation of Islamic banking windows - Algeria case study - أشرف دوابه, (Journal of North African Economies, 2025)
With the issuance of Regulation No. 2-2020 governing Islamic banking in Algeria, and the issuance of Instruction No. 3-2020 related to this regulation, a problem appeared about to the adequacy of it in building of Islamic banking windows which performs its work efficiently and effectively, as well as the ability of this system to meet the complete transformation of traditional banks to Islamic banks, in addition to the establishment of new Islamic banks. In this context, this research tries to evaluate Regulation No. 2-2020 which governs Islamic banking in Algeria, as well as Instruction No. 3-2020, through an analytical study of their provisions, in a way that reflects the positive and negative points regarding to Islamic banking windows, and then highlights the importance of the central bank to support these windows